1992
DOI: 10.1073/pnas.89.19.9049
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of interleukin 8 gene expression in human fibroblasts: unique mechanism of transcriptional inhibition by interferon.

Abstract: The chemotactic cytokine interleukin 8 (IL-8) is produced upon stimulation by various agents in many cell types, including connective-tissue fibroblasts. Tumor An earlier study described a set of genes activated by TNF in human fibroblasts (8). Some of the genes activated by TNF were also inducible by IFN-,3 or IFN-y. In contrast, IFN-,B or IFN-y inhibited the TNF-induced expression of one of these genes, termed TSG-1. Sequencing of the TSG-1 cDNA revealed that this gene was identical to the gene encoding an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
83
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(90 citation statements)
references
References 27 publications
7
83
0
Order By: Relevance
“…Similar to the GCP-2 induction, the IL-8 production induced by TNF-␣ was decreased by IFN-␥. These findings confirm the previously observed inhibition of TNF-␣-induced IL-8 mRNA expression by IFN-␤ and IFN-␥ in fibroblasts (Lee et al, 1990;Oliveira et al, 1992). Furthermore, IFN-␥ has been shown to inhibit TNF-␣-induced IL-8 production in endothelial cells (Nyhlén et al, 2000).…”
Section: Regulation Of Gcp-2 In Connective Tissuesupporting
confidence: 91%
“…Similar to the GCP-2 induction, the IL-8 production induced by TNF-␣ was decreased by IFN-␥. These findings confirm the previously observed inhibition of TNF-␣-induced IL-8 mRNA expression by IFN-␤ and IFN-␥ in fibroblasts (Lee et al, 1990;Oliveira et al, 1992). Furthermore, IFN-␥ has been shown to inhibit TNF-␣-induced IL-8 production in endothelial cells (Nyhlén et al, 2000).…”
Section: Regulation Of Gcp-2 In Connective Tissuesupporting
confidence: 91%
“…As early as 1980, IFN had been shown to inhibit endothelial cell motility [58], and later in the 1980s was shown to inhibit tumor-and allogeneic lymphocyte-induced angiogenesis [59] and to selectively damage the tumor microvascular endothelium, leading to coagulation necrosis of murine tumors selected for resistance to IFN's antiproliferative effects [60]. Further investigations of the angiogenesis inhibitory activities of IFN in the 1990s showed that IFNα could downregulate IL-8 production in fibroblasts [61] and bFGF in human tumor cell lines resistant to IFN's antiproliferative effects [62]. Building upon the latter observation in studies of human tumors implanted in nude mice, Fidler and colleagues showed that optimal inhibition of tumor weight, microvessel density, and expression of bFGF, MMP-9 and IL-8 were obtained when low, daily IFN doses were administered, whereas inferior effects were observed when isodense doses were given less often, or when higher IFN doses were used [63][64][65].…”
Section: Angiogenesis Inhibitionmentioning
confidence: 99%
“…30,31 Its anti-angiogenic activity has been well established by a number of in vitro studies indicating that it can block endothelial cell migration, 8,32 and also downregulate angiogenic factor expression, such as bFGF, IL-8, MMP-2 and MMP-9. [33][34][35][36] IFN-␣ also down-regulates bFGF expression in human carcinomas. 34 However, we did not observe reduced expression of bFGF mRNA in the IFN-␣ 1 -producing MDA-MB435 cell line, neither in vitro (Figure 2c) nor in vivo (data not shown), as evaluated by RT-PCR experiments.…”
Section: Figure 7 Angiostatin Expression In Mcf7 and Mda-mb435 Tumorsmentioning
confidence: 99%